An electrophoretic mobility shift assay with chemiluminescent readout to evaluate DNA-targeting oligonucleotide-based probes - Michaela E. Everly; Peter J. Wieber; Ibrahim Al Janabi; Patrick J. Hrdlicka (PLoS ONE, 2025)
A comprehensive and user-friendly method for evaluating recognition of double-stranded DNA (dsDNA) targets by oligonucleotide-based probes is presented. Thus, dsDNA-targeting probes such as single-stranded locked nucleic acids (LNAs) and double-stranded Invader probes are incubated with digoxigenin-labeled DNA hairpin targets, and the resulting recognition complexes are resolved using an electrophoretic mobility shift assay and tagged using a chemiluminescence immunoassay. Emissive products are detected by a C-DiGit Blot Scanner and quantified with the accompanying software. R-based scripts for data visualization and determination of C 50 values (a measure of the dsDNA-binding affinity of a probe) are also provided. The data presented here demonstrate the effectiveness of the described protocol and highlight the variable dsDNA-recognition efficiencies of LNAs, Invader probes, and chimeric Invader:LNA probes.